2017
DOI: 10.1111/vsu.12634
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic limb kinematics in the dog with and without a stifle orthosis

Abstract: The restrictive motion of the stifle orthosis is not fully translated to the underlying joint, based on the limited differences between the motion of braced and unbraced stifles. This effect varies with plane of motion and phase of the gait cycle, with most changes in stifle motion being detected during the stance phase. The stifle orthosis had an equal or greater effect on the motion of adjacent joints, especially the tarsus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…A study by Murakami et al showed that the level of constraint created by device affects the ground reaction force pattern (21). Additionally, Torres et al showed that the application of a stifle orthosis affected the kinematics for all joints and planes of motion at a walk and trot (22). This may specifically explain the noteworthy discrepancy between the improvement in TO with the device donned and without, as the tarsal devices induced a variable level of constraint based on the injury.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Murakami et al showed that the level of constraint created by device affects the ground reaction force pattern (21). Additionally, Torres et al showed that the application of a stifle orthosis affected the kinematics for all joints and planes of motion at a walk and trot (22). This may specifically explain the noteworthy discrepancy between the improvement in TO with the device donned and without, as the tarsal devices induced a variable level of constraint based on the injury.…”
Section: Discussionmentioning
confidence: 99%
“…Kinematic changes associated with joint disorders and treatments are commonly quantified with marker-based motion capture systems (Böddeker et al, 2012;Torres et al, 2017). For instance, with marker-based gait analysis, Böddeker et al (2012) found that, compared to the preoperative values, the stifle extension angle of cranial cruciate ligament-deficient dogs increased approximately 5 postoperatively throughout the gait cycle.…”
Section: Notementioning
confidence: 99%
“…Bajo la luz de lo anterior, a nivel mundial, muchas Instituciones de Educación Superior y centros de investigación han desarrollado prototipos de interés, siguiendo metodologías del proceso de diseño, análogas entre sí, y que parten de la investigación de referentes que sirven para generar diversas alternativas de mecanismos, materiales y estética. En este sentido, países como España, Estados Unidos, Israel, Rusia y Suecia han direccionado esfuerzos para desarrollar dispositivos de inmovilización para animales, específicamente perros, como se muestra en varios trabajos, como por mencionar algunos, los de Antonana et al (2019); Popov et al (2019); Torres et al (2017); Wagoner et al (2018); Mesa (2020) y Pascual , todos direccionados a resolver el problema de movilidad y marcha del animal, utilizando como herramienta principal la manufactura aditiva (impresión 3D). A pesar de ello, muchos son equipos complejos con sensores electrónicos y con conectividad móvil, otros poseen componentes de electroestimulación para acelerar la recuperación del usuario y en otros casos, utilizan materiales especiales como la fibra de carbono.…”
Section: Introductionunclassified